Teoria da asserção e o direito fundamental à prestação jurisdicional - Beserra, Karoline Mafra Sarmento (2013)
The aim of this study was to analyze the application of the assertion theory as a way to ensure an immediate and effective judicial protection. By means of the procedural autonomy, civil action is defined as the right to ask court an answer to the pleadings addressed to it, regardless of the existence of the substantive law. On account of the inquiry of the theories on the subject of the conditions to exercise capacity to pursue judicial proceedings, several discernments arise as the result of the search to delimitate its legal nature, since the Code of Civil Procedure adopted the eclectic theory of action, whereas the lawsuit is seen as the right for an answer to the claims made in court. Nevertheless, these concepts should be reviewed. Access to Justice as a fundamental right is stipulated in article 5, XXXV, of the Brazilian Federal Constitution, therefore under-constitutional law must not exclude from judicial review any injury or threat to injury to any given right. Consequently, in a preliminary view, the action constitutional guarantees consists in ensuring, therefore, the lawsuit itself, the right to act, the right to exercise a citizenship, the access to a fair, adequate and effective juridical order. Therefore it is essential that the judge is aware of this reality, in order to apply the procedural techniques that best suits the requirements of the substantive law, due to the fundamental right to an effective jurisdiction concerning the requirements for exercising civil action, since procedural law establishes such conditions for a proper judicial answer to the subjective right. Depending on what moment the conditions for exercising a legal demand are analyzed by the judge, doctrine varies to consider them a preliminary issue or question of merit, thus influencing, the nature of the jurisdictional provision. For that reason, we Will briefly review the constitutional precept of access to justice and procedural limitations established by the conditions of action. We will ascertain the eclectic theory adopted by systematic procedural and we will conclude with the doctrinal and jurisprudential understanding that the courts have been giving shelter to the theory of assertion, seeking to ensure a swift and active judicial protection.